Effects of Ursolic Acid and its Analogues on Soybean 15-Lipoxygenase Activity and the Proliferation Rate of A human Gastric Tumour Cell Line - D. Es-Saady; A. Najid; A. Simon; Y. Denizot; A. J. Chulia; C. Delage (Hindawi Limited, 1994)
The authors have previously isolated and purified ursolic acid from heather flowers (Calluna vulgarts). This terpene was found to inhibit HL-60 leukaemic cell proliferation and arachidonic acid oxidative metabolism in various cell species. The effects of ursolic acid and its analogues on soybean 15-lipoxygenase activity and on the proliferation of a human gastric tumour cell line (HGT), have been assessed. These triterpenes inhibited soybean 15-lipoxygenase at its optimal activity (pH 9). The proliferation ofHGT was decreased in a dose-dependent manner. At 20 μM the rank order is: ursolic acid > uvaol > oleanolic acid > methyl ursolate. The carboxylic group at the C28 position of ursolic acid appears to be implicated in the inhibition of both lipoxygenase activity and cell proliferation. Thus methylation of this group decreases these two inhibitory properties. Oleanolic acid, which differs by the position of one methyl group (C20 instead of C19) is less inhibitory than ursolic acid. The lipophilicity of the terpene is also implicated since uvaol appears to be more inhibitory than methyl ursolate.